2020
DOI: 10.1016/j.isci.2020.101777
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Post-gastric Bypass Intestinal Microenvironment Uncovers a Barrier-Stabilizing Role for FXR

Abstract: Summary Regional changes to the intestinal microenvironment brought about by Roux-en-Y gastric bypass (RYGB) surgery may contribute to some of its potent systemic metabolic benefits through favorably regulating various local cellular processes. Here, we show that the intestinal contents of RYGB-operated compared with sham-operated rats region-dependently confer superior glycemic control to recipient germ-free mice in association with suppression of endotoxemia. Correspondingly, they had direct barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 112 publications
0
6
0
Order By: Relevance
“…In animal models, RYGB-operated rats not only consumed less food and weighed less, but also had lower LPS and fasting plasma insulin levels in comparison to sham-operated rats [50]. Similar effects on LPS plasma levels were noted in a study involving ZDF (Zuker Diabetic Fatty) rats, in which obesity and its complications were genetically induced.…”
Section: Influence Of Bariatric Surgery On Gut Microbiota and Endotox...mentioning
confidence: 55%
“…In animal models, RYGB-operated rats not only consumed less food and weighed less, but also had lower LPS and fasting plasma insulin levels in comparison to sham-operated rats [50]. Similar effects on LPS plasma levels were noted in a study involving ZDF (Zuker Diabetic Fatty) rats, in which obesity and its complications were genetically induced.…”
Section: Influence Of Bariatric Surgery On Gut Microbiota and Endotox...mentioning
confidence: 55%
“…The results demonstrated that the treatment of BoA2C obviously reduced the migration of MCF-7 cells in the scratch compared to control group, thus potentially inhibited tumor invasion with enhanced FXR expression. Then, a potent FXR antagonist (DY268) was employed ( Yu et al, 2014 ; Hankir et al, 2020 ) in a cell proliferation investigation to better evaluate the regulatory link between FXR expression and BoA2C treatment. The results ( Figure 8B ) unequivocally demonstrated that DY268 reversed BoA2C inhibitory impact on the growth of MCF-7 breast cancer cells in both 24, 48 and 72 h. Thus, BOA2C could disrupt bile acid and fatty acid metabolism and limit tumor development and invasion probably by activating FXR expression.…”
Section: Resultsmentioning
confidence: 99%
“…As well as favorable shifts in the intestinal microbiota, the improvements in glycemic control caused by RYGB have been partly attributed to an overall attenuation of systemic endotoxemia [ 11 , 12 , 13 , 14 , 15 ]. While the underlying molecular and cellular mechanisms presently remain unclear, we previously found that transfer of jejunal and colonic content from RYGB-treated compared with sham-operated rats to germ-free mice improved oral glucose tolerance in association with suppression of systemic endotoxemia [ 26 ]. This suggests that jejunal and colonic microbiota-generated metabolites, including secondary bile acids, overall reduce intestinal permeability following RYGB when glycemic control is improved [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the underlying molecular and cellular mechanisms presently remain unclear, we previously found that transfer of jejunal and colonic content from RYGB-treated compared with sham-operated rats to germ-free mice improved oral glucose tolerance in association with suppression of systemic endotoxemia [ 26 ]. This suggests that jejunal and colonic microbiota-generated metabolites, including secondary bile acids, overall reduce intestinal permeability following RYGB when glycemic control is improved [ 26 ]. In contrast, it can be speculated that RYGB-associated ileal microbiota tip the balance in the other direction during relapse of type 2 diabetes to exert a dominant (negative) effect on systemic endotoxemia, which remains to be formally tested.…”
Section: Discussionmentioning
confidence: 99%